Language errors in Hebrew: (Reasons and motives) - Rheama, Mageed Aboud (Al-Adab Journal, 2020)
This research sheds light on a central and important topic in the Hebrew language, “Linguistic Mistakes in Hebrew” in Hebrew newspapers and articles, and how to address them by indicating their correct rules.Hebrew grammar is one of the important means of ordering a sentence, Articles and newspapers, in Hebrew, are full of grammatical errors, which undoubtedly affect the quality of translation and the loss of its true meaning. The purpose of this study is to identify errors to avoid making them. And fix them by identifying selected examples of different Hebrew textsThis research included an introduction, which dealt with the most prominent linguistic errors among specialists in the Hebrew language, followed by this introduction a brief overview of how to correct these errors as well as we studied important aspects of the causes of these errors and how to address them linguistically, and at the end of the research conclusions reached through my study of these Mistakes.